The very Hungry Caterpillar: Story Reading as an Effective Strategy Toward Achieving Proficiency in Efl in very Young Learners - Edita Hornackova Klapicova; Megan Reister (The Francis de Sales Scientific Society (TNFS.PL), 2022)
This article examines how the use of music, tangible objects, story-reading, hands-on activities, drama activities, and Readers Theater strategy can help very young learners to become proficient in English as a foreign language. The present study is based on an English lesson taking place in a kindergarten in Lower Austria. There were two target groups of three to six year old children, one consisting of 25 learners and one consisting of 24 learners. English as a second language was taught to them in a naturalistic way for the period of three years. The learners' language skills and communicative competence in English were assessed through three different oral tests during the lesson. The results of the tests proved that the learners had already acquired a high level of proficiency in EFL as a result of the effective teaching strategies used in their English program and were capable of acquiring new vocabulary and meanings during the current English lesson